Integrasi Nilai Syariah dalam Perencanaan dan Pengelolaan Sumber Daya Manusia: Studi Literatur - Syamsiah, Sitti; Parmitasari, Rika Dwi Ayu; Syariati, Alim (Assyarikah: Journal of Islamic Economic Business, 2025)
This study discusses the importance of human resource management and planning in organizations based on Islamic values. The research uses a literature review method by analyzing scientific journal articles obtained through academic databases. The results of the review show that human resources are a strategic factor in achieving organizational goals, both operationally and strategically. Islamic-based not only emphasizes administrative efficiency but also the importance of human values, justice, professionalism, and spirituality. Values such as justice, transparency, consultation, excellence, and consistency play a role in shaping an Islamic work culture that supports employee motivation, commitment, and integrity. Thematic analysis leads to the development of a holistic Islamic HR management framework that can be applied in recruitment, training, and evaluation processes. These findings provide practical contributions for Islamic educational and financial institutions to align HR policies with Sharia principles while strengthening organizational competitiveness through employee ethics and well-being.